2021
DOI: 10.1108/jima-03-2020-0076
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of gender and religiosity on the EMA model: an Indonesian Muslim pilgrim perspective

Abstract: Purpose This paper aims to investigate the relationship between expectations of umrah visit, the two dimensions of motivation for umrah visit and attitude toward umrah visit using the expectation, motivation and attitude (EMA) model. The study aims to expand the domain of religious tourism and destination marketing by including the moderating role of gender and religiosity on the EMA model to investigate the pre-visit stage of Indonesian Muslim pilgrims. Design/methodology/approach An online survey for 299 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 103 publications
3
8
0
Order By: Relevance
“…Hence, it also verifies the role of religion to bridge people's minds and economic and social values. This study confirmed preliminary studies that religion is still an essential key point among people to adopt a product and service rather than materialism (Minton and Liu, 2020;Nugraha and Widyaningsih, 2021;Zakaria, et al, 2021). However, religiosity is less significant than materialism to influence the people to adopt a product that complies with the religious brand in India (Islam and Chandrasekaran, 2019), Indonesia (Junaidi et al, 2021) and Malaysia (Jan and Shafiq, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…Hence, it also verifies the role of religion to bridge people's minds and economic and social values. This study confirmed preliminary studies that religion is still an essential key point among people to adopt a product and service rather than materialism (Minton and Liu, 2020;Nugraha and Widyaningsih, 2021;Zakaria, et al, 2021). However, religiosity is less significant than materialism to influence the people to adopt a product that complies with the religious brand in India (Islam and Chandrasekaran, 2019), Indonesia (Junaidi et al, 2021) and Malaysia (Jan and Shafiq, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…As depicted in Table 3, the estimated coefficients of gender variables are statistically significant at a 5% level of significance in model 3, 4, and 5, and 10% level of significance in model 1,2, and 6. This finding has confirmed Nugraha and Widyaningsih (2021) study on Indonesian Muslim pilgrims, which found that gender significantly moderates the relationship between umroh visit expectation and attitude toward umrah visit. This result suggests that gender may likely have different levels of satisfaction towards the hajj services, particularly for the dimension service procedure (SP), speed of service (T), and ease of access to information.…”
Section: Resultssupporting
confidence: 85%
“…Some previous studies have also found a positive effect of social influence on individuals’ attitudes ( Chen et al, 2021 ; Yılmaz and Anasori, 2021 ). Nugraha and Widyaningsih (2021) have identified that individuals’ attitudes are influenced mostly by the expectation of the consumer. A recent study has come up with a similar result acknowledging that consumers’ attitudes are influenced by their social group’s perceptions of products ( Koo and Chung, 2014 ; Bratu, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%